HUBUNGAN KOORDINASI MATA-KAKI DAN KESEIMBANGAN DENGAN KETERAMPILAN SEPAK SILA PADA EKSTRAKURIKULER SEPAKTAKRAW SMK DAREL HIKMAH PEKANBARU - Ahmad Zulfahmi; zainur Zainur; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The aim of the research was to get the correlation of anklecoordination and balance with the ability of precepts kick on sepaktakrawextracurricular of SMK Darel Hikmah Pekanbaru. The forms of this research was the correlation study, the population in this study was sepaktakraw extracurricular of SMK Darel Hikmah Pekanbaru and the sample in this study was 9 students. While the sample tecnique used is total sampling (saturated sample), where all the population as the sample. So, the sample in this study amounted to 9 students. After that, the data isprocessed with statistics, normality test with liliefors test and correlation at significant level α (0,05). The first analysis in the calculation of the correlation between X1 and Y, where rtable at significant level α (0,05) = 0,707 means rresult (0,908) > rtable (0,707), which means the hypothesis is accepted and there is a meaningful correlation with a very strong interpretation between ankle coordination with the ability of precepts kickon students sepaktakraw extracurricular SMK Darel Hikmah Pekanbaru, a second analysis of in the calculation of the correlation between X2 and Y, where rtable at significant level α (0,05) = 0,707means rresult (0,872) > rtable (0,707), which means the hypothesis is accepted and there is a meaningful correlation with a very strong interpretation between balance with the ability of precepts kick on students sepaktakraw extracurricular SMK Darel Hikmah Pekanbaru. The analysis of the three correlation X1and X2 with Y was obtained, which rtable at significant level α (0,05) = 0,707, means Rresult (0,934) > rtable (0,707). Than it can be concluded that the correlation between X1 and X2 with Y or the correlation between ankle coordination with the ability of precepts kick on sepaktakraw extracurricular SMK Darel Hikmah Pekanbaru are significant.Key Words : Ankle Coordination, Balance dan Precepts Kick.